Irregular Migration IMISCOE Short Reader - Ambrosini, Maurizio (IMISCOE Research Series, 2023)
This open access short reader provides an introduction to the theoretical debates regarding irregular migration and aims to bridge these theoretical debates to current empirical developments. It defines irregular migrants and irregular migration by discussing the wide variety of definitions and highlights the reasons for the presence of irregular immigrants in developed countries. The book provides an overview of the variation in policies regarding irregular migrants and elaborates on how irregular migration is facilitated and supported. It discusses the trends and dynamics between border enforcement, human smuggling/trafficking, and on the support irregular migrants obtain by citizens and civil society while residing in the EU. Last but not least, the book also focuses on the agency and political mobilization of irregular migrants. As such, it provides a great resource for everyone interested in learning more about irregular migration.